Autonomy, Beneficence, andGezelligheid: Lessons in Moral Theory from the Dutch - Lindemann, Hilde (The Hastings Center report, 2009)
American bioethicists lack the theoretical resources to work in cross-cultural settings. All we have are two approaches to ethics—principles vs. narratives—that are mostly at odds, and neither of which is up to the job. If moral principles are too abstract to be useful, and if stories cannot provide moral authority, then where do we find our moral norms?